Extra-Heavy Oil Aquathermolysis Using Nickel-Based Catalyst: Some Aspects of In-Situ Transformation of Catalyst Precursor - Alexey V. Vakhin (Catalysts, 2021)
In the present work, we studied the catalytic performance of an oil-soluble nickel-based catalyst during aquathermolysis of oil-saturated crushed cores from Boca de Jaruco extra-heavy oil field. The decomposition of nickel tallate and some aspects of in-situ transformation of the given catalyst precursor under the steam injection conditions were investigated in a high-pressure batch reactor using XRD and SEM analysis methods. The changes in physical and chemical properties of core extracts after the catalytic aquathermolysis process with various duration were studied using gas chromatography for analyzing gas products, SARA analysis, GC-MS of saturated and aromatic fractions, FT-IR spectrometer, elemental analysis, and matrix-activated laser desorption/ionization (MALDI). The results showed that nickel tallate in the presence of oil-saturated crushed core under the injection of steam at 300 °C transforms mainly into nonstoichiometric forms of nickel sulfide. According to the SEM images, the size of nickel sulfide particles was in the range of 80–100 nm. The behavior of main catalytic aquathermolysis gas products such as CH4, CO2, H2S, and H2 depending on the duration of the process was analyzed. The catalytic upgrading at 300 °C provided decrease in the content of resins and asphaltenes, and increase in saturated hydrocarbon content. Moreover, the content of low-molecular alkanes, which were not detected before the catalytic aquathermolysis process, dramatically increased in saturates fraction after catalytic aquathermolysis reactions. In addition, the aromatics hydrocarbons saturated with high molecular weight polycyclic aromatic compounds—isomers of benzo(a)fluorine, which were initially concentrated in resins and asphaltenes. Nickel sulfide showed a good performance in desulfurization of high-molecular components of extra-heavy oil. The cracking of the weak C–S bonds, which mainly concentrated in resins and asphaltenes, ring-opening reactions, detachment of alkyl substitutes from asphaltenes and inhibition of polymerization reactions in the presence of catalytic complex reduced the average molecular mass of resins (from 871.7 to 523.3 a.m.u.) and asphaltenes (from 1572.7 to 1072.3 a.m.u.). Thus, nickel tallate is a promising catalyst to promote the in-situ upgrading of extra-heavy oil during steam injection techniques.